2019
DOI: 10.1002/prep.201900286
|View full text |Cite
|
Sign up to set email alerts
|

OZM Ball Drop Impact Tester (BIT‐132) vs. BAM Standard Method – a Comparative Investigation

Abstract: Safety, performance, cost efficient synthesis and toxicity are the most important aspects of modern explosives. Sensitivity measurements are performed in accordance with different protocols all around the world. Sometimes the BAM drop hammer does not accurately reflect the sensitivity of an energetic material, in particular the sensitivity of primary explosives. Therefore, we present here preliminary results obtained using the novel ball drop tester (BIT‐132), manufactured by OZM research, following MIL‐STD‐17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…In addition, measurements of the salts’ sensitivity toward ball drop impact according to MIL-STD 1751A (method 1016) were carried out. , This type of impact test is intended to produce more realistic results, because a combination of friction and impact is applied to the substance . It was found that substances less sensitive toward friction were also less sensitive toward the ball drop impact test.…”
Section: Results and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, measurements of the salts’ sensitivity toward ball drop impact according to MIL-STD 1751A (method 1016) were carried out. , This type of impact test is intended to produce more realistic results, because a combination of friction and impact is applied to the substance . It was found that substances less sensitive toward friction were also less sensitive toward the ball drop impact test.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…A slight correlation between ball drop impact sensitivity and BAM impact sensitivity was observed in the case of compound 18 (BDIS = 28 mJ, IS ≤ 1 J) but not for the only slightly less sensitive complexes 16 (BDIS > 200 mJ, IS = 2 J), 17 (BDIS = 200 mJ, IS = 2 J), and 20 (BDIS > 200 mJ, IS = 9 J) (Figure ). A correlation between sensitivity toward friction was also not observed in the case of the ECCs, which is contrary to our earlier findings …”
Section: Results and Discussionmentioning
confidence: 99%
“…For the most commonly used primary explosives lead azide (LA RD‐1333) and lead styphnate (LS) these sensitivities were determined to 0.45–1 N and 7–8 J (LS) as well as ≤0.1 N and 4 J (LA RD‐1333). [ 34 , 35 ] For explosives ignited by laser irradiation, however, less sensitive substances are also suitable, which drastically reduces the risk potential during production, processing, and storage of the respective energetic materials.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivities obtained for compounds 5 (IS = 8 J, BDIS > 200 mJ, FS = 120 N), 6 (IS = 2 J, BDIS = 28 mJ, FS = 5 N), 7 (IS = 2 J, BDIS > 28 mJ, FS = 3 N), 13 (IS = 2 J, BDIS = 180 mJ, FS = 120 N), and 15 (IS = 3 J, BDIS > 200 mJ, FS = 240 N) are either very low, or very high, which is consistent with our earlier findings. [34] It is assumed that there is a strong correlation between low sensitivity toward friction and ball drop impact. However, in the case of compounds 2, 3, and 11 the results do not match our previous results.…”
Section: Nomentioning
confidence: 99%
“…While computational models and simulations have been developed in order to predict energetic material sensitivity, empirical data are still required for accurate assessments. Many methods are available for the sensitivity testing of energetics; however, varying analysis and instrumentation can make comparison of those results difficult. Despite efforts by the United Nations to standardize many of these sensitivity tests, variations in testing conditions can result in a range of values for a particular energetic, particularly when it comes to impact testing.…”
Section: Introductionmentioning
confidence: 99%